Bioactive Components From Gracilaria rubra With Growth Inhibition on HCT116 Colon Cancer Cells and Anti-inflammatory Capacity in RAW 264.7 Macrophages - Yi, Lingxiao; Wang, Qi; Luo, Haiyan; Lei, Daqing; Tang, Zhonghai; Lei, Sijia; Xiao, Hang (Frontiers in Nutrition, 2022)
Gracilaria rubra is rich in bioactive compounds with various potential health benefits. The work aimed to elucidate the profile of both extractable bioactive components (EBCs) and non-extractable bioactive components (NEBCs) of G. rubra, and determine their anti-colon cancer and anti-inflammatory activities. Both EBCs and NEBCs displayed strong suppressive effects on the viability of HCT116 cells, causing cell cycle arrest, inducing cellular apoptosis and regulating the expression of cyclin-dependent kinases and tumor suppressor proteins. Additionally, EBCs and NEBCs from G. rubra displayed anti-inflammatory functions via inhibiting the production of nitric oxide (NO), reactive oxygen species (ROS), proinflammatory cytokines in activated macrophages, and regulating expression levels of cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), NADPH-quinone oxidoreductase-1 (NQO-1) and heme oxygenase 1 (HO-1). These findings provide a rationale for animal and human studies designed to evaluate the chemopreventive and anti-inflammatory potential of these bioactive compounds from G. rubra.